MODERN ASPECTS OF FEVER MANAGEMENT: Srpski - Pavlovic Jugovic, Katarina; Radovanovic, Jovana; Jaksic, Stefan (HEALTH CARE, 2023)
The aim of this review article was to present in a systematic way modern aspects of body temperature management. A fever is one of the oldest, best known and best observed manifestations of the disease. It is a normal, coordinated body’s response to an identified threat to the immune system, including the autonomic, behavioral and neuroendocrine response. Fever management is an integral aspect of health care at all levels of health care. There are two basic approaches to solving this problem: pharmacological and physical care. Uncontrolled conventional methods, intravascular and percutaneous controlled methods are available within physical methods of care, while pharmacological methods most frequently include the use of antipyretics.